Mclintock!. - McLaglen, Andrew V.; Wayne, John; O'Hara, Maureen; Wayne, Patrick
GW, a cattle baron, has been waiting for his daughter to return. To his surprise, his wife, Katherine, has also returned after a two-year separation only to seek a divorce from her husband.